A rapid method for screening 90Sr activity in water and milk samples using Cherenkov radiation - Stamoulis, K. C.; Ioannides, K. G.; Karamanis, D. T.; Patiris, D. C. (HNPS Advances in Nuclear Physics, 2019)
Strontium-90 is one of the most dangerous fission products that enter the food chain. Because of its similar chemistry to calcium, it is deposited to bones posing a high risk for human health. 90Sr is a pure ^-emitter and decays to 90Y also a /3-emitter. The fast moving electrons emitted by the 90Y decay, produce Cherenkov radiation, which can be detected by a Liquid Scintillation Counter (LSC). Water and milk samples spiked with various concentrations of 9 0Sr/90Y in equilibrium were measured in a LSC (Tricarb 3170 TR/SL). The derived efficiencies were 50% for water samples and 13 % for milk samples. The minimum detectable activities (MDA) for measuring 90Sr in water and milk samples, without any pretreatment were calculated 240 mBq/L and 1 Bq/L respectively. The intervention levels for 90Sr contamination in water and milk samples, established by the European Union are 125 Bq/L and 75-125 Bq/L depending on age, respectively. The interference of 40K, which is present in milk due to its natural potassium content,was also investigated.